(untitled) (BIRDEM Medical Journal, 2016)
Background and Objectives: Diabetes in the young patients, less than 30 years of age, usually has sudden onset and severe hyperglycemia who are resistant to ketosis. Taking the advantage of this uniqueness of this group of patients the present study was aimed to evaluate their peripheral nerve functional status, explore its relationship with glycemic status and find out utility of nerve conduction study for detection of neuropathy at diagnosis to introduce timely intervention in the necessary cases. Materials and Methods: A total number of 32 newly diagnosed untreated diabetic patients, age 30 years or less, consecutively attending the BIRDEM Out-patient department were recruited. Age-matched healthy subjects (n=30) with no family history of diabetes served as controls. Motor and sensory conduction velocities (NCV), distal latencies (DL), compound muscle and sensory nerve action potentials (CAMP, SNAP) of ulnar, peroneal and sural nerves were studied following standard protocol. Glucose was determined by glucose-oxidase, Fructosamine by enzymatic colorimetric method. Results: Ulnar motor NCV (m/sec, mean±SD) was significantly slower in diabetic group compared to the controls [58.29±6.88 vs 66.56±6.13; p<0.001]. CAMP [(?v, median] of ulnar nerve was significantly lower in diabetic patients [4.5 vs 5.8; p<0.05]. Motor nerve conduction velocity of peroneal nerve was significantly slower (p<0.0001) in diabetic patients. Peroneal nerve CMAP [?v, median] amplitude showed similar trends [5.5 vs 8.7 p<0.001]. Sural sensory NCV was significantly slower [35.22±14.04 vs 42.38±8.52; p<0.05] in diabetic patients. Peroneal nerve conduction velocity showed significant negative correlation with fasting glucose (r= -0.456, p<0.001). Peroneal motor distal latency showed positive correlation with serum fructosamine value [r=0.439, p<0.05]. Peroneal and ulnar NCV was negatively correlated [p<0.001 and p<0.05 respectively] with fructosamine. Sural sensory nerve action potential was also negatively correlated [r=-0.400 p<0.05]. S. Fructosamine was negatively correlated with sensory ulnar nerve action potential. Conclusion: The result suggest that in the newly diagnosed untreated young diabetics of Bangladesh, abnormalities of nerve conduction parameters are detected early by doing nerve conduction study; motor nerve conduction parameters are affected more than sensory ones. Abnormal nerve conduction parameters seem to be related to degree of hyperglycaemia in early neuropathic patients. Birdem Med J 2015; 5(1): 14-19